2011
DOI: 10.1002/ar.21467
|View full text |Cite
|
Sign up to set email alerts
|

Jaw Adductor Muscles across Lepidosaurs: A Reappraisal

Abstract: The exact homologies of tetrapod jaw muscles remain unresolved, and this provides a barrier for phylogenetic analysis and tracing character evolution. Here, lepidosaur jaw muscles are surveyed using direct examination of species from 23 families and published descriptions of species from 10 families. A revised nomenclature is applied according to proposed homologies with Latimeria. Among lepidosaurs, variation was found in many aspects of jaw muscle anatomy. The superficial layers mm. levator and retractor ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…Both have concluded that this part of the muscle is better regarded as MAME medialis, the muscle that in lizards inserts on the lateral face of the Bodenaponeurose, but Haas () desisted from renaming it in the interest of consistency with other literature. The solution adopted here, MAME superficialis, is consistent with the situation in Sphenodon and lizards (Daza et al, ), turtles (Jones et al, ), crocodilians, and birds (Holliday and Witmer, ) in which a muscle inserts over a broad area on the lateral face of the mandible—this represents the most lateral, caudal end of the folded sheet morphology. In addition, the finding of continuity or near‐continuity of the MAME superficialis and MAME medialis, for example in Antaresia (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Both have concluded that this part of the muscle is better regarded as MAME medialis, the muscle that in lizards inserts on the lateral face of the Bodenaponeurose, but Haas () desisted from renaming it in the interest of consistency with other literature. The solution adopted here, MAME superficialis, is consistent with the situation in Sphenodon and lizards (Daza et al, ), turtles (Jones et al, ), crocodilians, and birds (Holliday and Witmer, ) in which a muscle inserts over a broad area on the lateral face of the mandible—this represents the most lateral, caudal end of the folded sheet morphology. In addition, the finding of continuity or near‐continuity of the MAME superficialis and MAME medialis, for example in Antaresia (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…There is however some variability in the number of tooth positions among extant amphisbaenians. Thus, a count of nine dentary teeth has been also reported for several species of Amphisbaena , such as Amphisbaena fuliginosa [61], and it is also observable in the Amphisbaena alba figured in the literature [62], [63]. We further report a posteriorly located ninth small tooth in an extant Blanus strauchi dentary from Vic Siirt (Turkey) in the S. Bailon personal collection.…”
Section: Resultssupporting
confidence: 65%
“…The main diagnostic character is the presence of nine dentary teeth, rather than a maximum of eight as in other amphisbaenians (Smith, 2009a). However, at least one specimen of Amphisbaena alba from Bolivia also has nine dentary teeth (Figure 11, p. 1774 in Daza et al, 2011), and the original description of Anniealexandria (Smith, 2009a) noted similarities with Amphisbaena.…”
Section: Amphisbaenia Gray 1844mentioning
confidence: 99%